2023
DOI: 10.1101/2023.11.02.565407
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative Three-dimensional Label-free Digital Holographic Imaging of Cardiomyocyte Size, Ploidy, and Cell Division

Sangsoon Park,
Herman Huang,
Ines Ross
et al.

Abstract: Cardiac regeneration in newborn rodents depends on the ability of pre-existing cardiomyocytes to proliferate and divide. This capacity is lost within the first week of postnatal development when these cells rapidly switch from hyperplasia to hypertrophy, withdraw from the cell cycle, become binucleated, and increase in size. How these dynamic changes in size and ploidy impact cardiomyocyte proliferative potential is not well understood. In this study, we innovate the application of a commercially available dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The following segmentation thresholds were applied: auto-minimum error method, adjustment 134, and minimum object size 17. Cardiomyocytes were qualitatively distinguished from non-cardiomyocytes based on their larger size and limited motility as previously described [13]. Care was taken to track well-isolated cells that remained unambiguous throughout the entire imaging duration.…”
Section: Single-cell Tracking Of Surface Area and Optical Volume Dyna...mentioning
confidence: 99%
See 1 more Smart Citation
“…The following segmentation thresholds were applied: auto-minimum error method, adjustment 134, and minimum object size 17. Cardiomyocytes were qualitatively distinguished from non-cardiomyocytes based on their larger size and limited motility as previously described [13]. Care was taken to track well-isolated cells that remained unambiguous throughout the entire imaging duration.…”
Section: Single-cell Tracking Of Surface Area and Optical Volume Dyna...mentioning
confidence: 99%
“…Cardiac cultures from neonatal rat hearts are often contaminated with other cell types in addition to cardiomyocytes, despite methods used to increase purity [16,17]. Our lab has recently observed that α-actinin-positive cardiomyocytes can be distinguished from non-cardiomyocyte cells imaged on the Holomonitor M4 based on their overall larger size and slower motility [13] (Figure 1B). Using these criteria, we were able to readily identify cardiomyocytes in our cardiac cultures, both with and without norepinephrine treatment (Movies S1 and S2).…”
Section: Validation Of the Holomonitor M4 Digital Holographic Imaging...mentioning
confidence: 99%